An Erbium Fiber Laser With Single-Frequency Oscillation and Wavelength-Upconverted Output - Chien-Hung Yeh; Wei-Yao You; Jhao-Ren Chen; Chi-Wai Chow; Wen-Piao Lin (IEEE Photonics Journal, 2020)
In this paper, we present experimentally an erbium-doped fiber (EDF) laser system to accomplish the single-longitudinal-mode (SLM) and wavelength-upconverted output by using nonlinear effect. To accomplish the SLM output, a short length of unpumped EDF saturable absorber (SA) is applied inside the EDF laser cavity for filtering densely multi-mode noise. In accordance with the designed EDF laser system, the lasing wavelength can be upconverted to a longer wavelength position. In addition, the output characteristics of output power, optical signal to noise ratio (OSNR), tunability, stability and linewidth in the EDF laser are also discussed.